Comparison of Four Different Pain Relief Methods during Hysterosalpingography: A Randomized Controlled Study - Bekir Serdar Unlu; Mehmet Yilmazer; Gulengul Koken; Dagistan Tolga Arioz; Ebru Unlu; Elif Dogan Baki; Cemile Kurttay; Osman Karacin (Pain Research and Management)
BACKGROUND: Hysterosalpingography (HSG) is the most commonly used method for evaluating the anatomy and patency of the uterine cavity and fallopian tubes, and is an important tool in the evaluation of infertility. The most frequent side effect is the pain associated with the procedure.